A study of mobile robot motion control using active force control - Tiong, Lung Huat (2016)
The project describes a new strategy to control the motion of wheeled mobile robot (WMR) using active force control (AFC) based on its capability to eliminate the presence of disturbances. A proportional derivative active force control (PDAFC) scheme is incorporating with artificial intelligent techniques, namely, fuzzy logic (FL) to effectively calculate the inertia matrix which is multiplied by acceleration to give the actual torque. The heading rotation of a wheeled mobile robot is not always perfect because the workspace of an object is normally filled with known or unknown disturbances. The robustness and effectiveness of the proposed control scheme are investigated and compared with traditional controller like PD controller. The simulation study verify that the proposed system is performing excellently even in the presence of uncertainties. The simulated system was validated through simulation study carried out on circle and leaf trajectory by using software interface (MATLAB / SIMULINK). The obtained results of AFC and PDAFC controller demonstrate better performance in comparison with PD controller.